Kryminalistyka na Uniwersytecie Wrocławskim 1946–2015 - Jaworski, Ryszard (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
W. Gutekunst began scientific research and teaching in the field of forensic sciences at the Faculty of Law of the University of Wrocław in 1946. Initially the research focused on dactyloscopy and later on handwriting examination, where W. Gutekunst also conducted expert examination. Apart from lecturing on forensic sciences, he wrote a coursebook, published twice 1965, 1974. In 1961 Z. Kegel began his academic research in the field of handwriting examination. The same year the Division of Forensic Science and Forensic Science Lab were established. In 1966 Z. Bożyczko expanded the research into forensic methodology pickpocketing, burglary. From 1970 the Division of Forensic Science functioned as part of the Institute of Criminology. New research was initiated — traffic safety. In 1975 the Division of Forensic Science acquired new facilities multimedia room, chemistry lab, darkroom, lecture rooms. A polygraph was bought in 1976 and polygraph expert examination began in 1978 R. Jaworski. In 1981 the Division changed its status into the independent Department of Forensic Science headed by Prof. Zdzisław Kegel. Since 1983 the Department has organised the Wrocław Symposia of Handwriting Examination the 16th Symposium took place in 2014. Postgraduate studies in forensic sciences were opened in the 1980s when Head of the Department was prof. dr hab. Z. Kegel. The field of research was expanded to include examination of pathological handwriting, examination of paper and inks, mainly with the use of non-damaging methods cooperation with the Faculty of Chemistry, University of Wrocław. The Department received a few grants including two on document examination and two on the use of a polygraph. Currently, in 2015, apart from continuing the ongoing research, the Department of Forensic Science has also undertaken new research: detecting threats of mental cruelty, national security, protection of cultural heritage. Dr. R. Jaworski has been Head of the Department since 2005.
Keywords: kryminalistyka; Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego; historia